Implementation of surface modified carbon cloth electrodes with biochar particles in microbial fuel cells - Wang, Chin Tsan; Sangeetha, Thangavel; Ding, De Quan; Chong, Wen Tong; Yan, Wei Mon (Taylor & Francis, 2018)
Microbial fuel cells (MFC) are bioelectrochemical reactors that convert chemical energy in organic substrates to electrical energy through catalytic reactions of microorganisms. The relationship between microorganisms and electrodes plays a vital role for effective functioning of an MFC. The physical and chemical properties of the electrodes are more crucial for a feasible MFC performance. Plain Carbon cloth (CC) and surface modified CC with four different sizes of Biochar (BC) particles such as 2 mm BC< 2, BC2-4, BC4-6, and BC6-10 were employed as anode electrodes in dual-chambered MFCs and their performance was compared. Results showed that the electrode with BC< 2 enhanced the MFC performance to with power density of 312 mWm−2 and BC6-10 facilitated the maximum COD degradation performance of 77% in the MFC both due to electrode properties like high porosity and large surface area. This study in general is a proof that BC has high feasibility for usage in MFC electrode modification studies.